The Making of TOGA (Family Medicinal Plants) and Its Utilization in Improving Public Health in Sumbergede Village - Farida Anwari; Dewi Rahmawati; Ivan Charles; Ramadhan Maulana Putra; Oktafia Damayanti; Nungky Taniasari; Arista, Arista Wahyu Ningsih; Elis Anita Farida; Bella Fevi Aristia; Yani Ambari (Universitas Kristen Cipta Wacana, 2024)
Family Medicinal Plants (TOGA) are plants that are grown in the yard and are efficacious as medicine. The plants planted in the mini garden are telang flowers, red binahong, and kumis kucing. The manufacture of TOGA serves as a means to bring medicinal plants closer to public health efforts, which include preventive efforts (prevention), promotive efforts (improving health degrees), and curative efforts (curing diseases). Based on the problems and potentials owned by Sumbergede village, Wringinanom District, Gresik Regency, several stages are carried out, namely coordinating the creation of a mini toga garden with the head of Sumbergede village, conducting a survey of the location where the TOGA mini park will be made, Preparing tools and materials to create a TOGA mini garden, Making a TOGA mini garden. The educational participants seemed enthusiastic about participating in this activity. Some participants were able to identify the types of TOGA around their homes and were motivated to add other kinds of TOGA. The use of TOGA is considered safer, more practical, and does not require much cost than the use of drugs from pharmacies. Through this activity, it is hoped that the community can be motivated to plant TOGA around their homes and increase the use of TOGA in the treatment of diseases with mild symptoms in the community. Family medicinal plants are very important because they concern the health aspect of the community of Sumbergede village.